2005
DOI: 10.1515/znc-2005-11-1211
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 4-n-Nonylphenol by Non-modified and CYP1A1- and CYP1A2-Transgenic Cell Cultures of Tobacco

Abstract: The metabolism of 14 C-4-n-nonylphenol ( 14 C-4-n-NP), as a model for the xenoestrogen nonylphenol, was investigated in three types of tobacco cell suspension cultures: one genetically non-modified culture (NT) and two cultures constitutively expressing human cytochrome P450 CYP1A1 or CYP1A2. With 1 mg l Ð1 of 14 C-4-n-NP and 24 h of incubation, the xenobiotic was transformed almost completely to glycosides. After glycosidic cleavage, 14 C-4-n-NP and several primary metabolites of 14 C-4-n-NP were liberated. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…They have different structures, have versatile catalytic properties, and have a wide range of substrates (Durairaj et al, 2016). Moreover, monooxygenases engagement in the breakdown of nonylphenol has been also confirmed in the microsomes of human liver (Deng et al, 2010), Atlantic salmon (Thibaut et al, 2002), as well as in tobacco cells (Berger et al, 2005). Our study has showed that in Metarhizium sp.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…They have different structures, have versatile catalytic properties, and have a wide range of substrates (Durairaj et al, 2016). Moreover, monooxygenases engagement in the breakdown of nonylphenol has been also confirmed in the microsomes of human liver (Deng et al, 2010), Atlantic salmon (Thibaut et al, 2002), as well as in tobacco cells (Berger et al, 2005). Our study has showed that in Metarhizium sp.…”
Section: Introductionsupporting
confidence: 80%
“…Moreover, in the elimination of NP by human liver cells, CYP450 was involved in the process of hydroxylation at the 1′ carbon position, identifying the metabolite 4-(1-Hydroxynonyl)phenol, di-TMS (Deng et al, 2010). In transgenic tobacco cell cultures, CYP450 enzymes were involved in hydroxylation of 4-n-NP at the 4′, 5′, 6′, 7′, and 8′ carbon positions of the aliphatic chain as well as in the hydroxylation of the aromatic ring (Berger et al, 2005).…”
Section: Effect Of 4-n-np On Cyp450 Activitymentioning
confidence: 99%
“…The authors assayed the ability of CYP6G1 to metabolise imidacloprid and DDT by functional expression in heterotrophic tobacco cell suspension cultures. This system had previously been shown to be successful in supporting activity of constitutively expressed human P450s CYP1A1, CYP1A2 and CYP3A4 and production of high amounts of oxidised xenobiotic metabolites, without requiring coexpression of human NADPH‐P450 reductase and cytochrome b 5 14–17. Two binary plant expression vectors, sp Dm 6g1 and sp Dm 6g1‐his, were constructed by cloning D. melanogaster Cyp6g1 without or with a 3′ His‐tag next to a constitutive promoter into plasmid spsma 15.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, we started by production of transgenic tobacco-cell-suspension cultures overexpressing human P450s CYP1A1 or CYP1A2 (under control of a constitutive promotor) [9]. These P450-transgenic in vitro systems were then used to examine the metabolism of the herbicides atrazine and metamitron [9], and the xenoestrogen nonylphenol [10]. Objectives were to elucidate metabolic pathways in the transgenic tobacco cultures, to produce higher amounts of the metabolites for identification, and to determine whether the xenobiotics studied are substrates of the respective human P450 isozyme.…”
mentioning
confidence: 99%